The Effects Of Professionalism, Digital Communication, Service Quality, And Consumer Trust On Purchase Decisions At Eyelash Beautysn.Id - nurhiqmah, siti; Nugraha, Andika Prasetya; syafitri, netti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to examine the effect of professionalism, digital communication, service quality, and consumer trust on purchase decisions at Eyelash Beautysn.Id. In the beauty service industry, particularly eyelash extension services, consumers face perceived risk due to the intangible nature of services and the sensitivity of the treatment area. Therefore, understanding the determinants of purchase decisions is essential for improving business competitiveness and customer retention. Materials and methods. This research employed a quantitative explanatory design with a survey approach. The population consisted of 720 customers of Eyelash Beautysn.Id, with a sample of 88 respondents selected for analysis. Data were collected using a structured questionnaire measured on a five-point Likert scale. The instrument was tested for validity and reliability before analysis. Classical assumption tests were conducted prior to multiple linear regression analysis. Hypotheses were tested using t-tests, F-tests, and coefficient of determination (R²). Results. The findings indicate that professionalism (Sig.=0.018), digital communication (Sig.=0.015), service quality (Sig.=0.031), and consumer trust (Sig.=0.031) each have a positive and significant effect on purchase decisions. Simultaneously, the four variables significantly influence purchase decisions (F-test Sig.=0.000). The model demonstrates a strong relationship (R=0.743) with an explanatory power of 55.2% (R²=0.552; Adjusted R²=0.531). Conclusions. Purchase decisions at Eyelash Beautysn.Id are significantly shaped by the integration of professional service execution, effective digital interaction, high service quality, and strong consumer trust. Strengthening these aspects in a consistent and integrated manner can enhance repurchase intentions and customer recommendations.